Lippia citrodora (Lemon Verbena) Extract Helps Reduce Stress and Improve Sleep Quality in Adolescents in a Double-Blind Randomized Intervention Study - Pau Navarro; Adrián García; Roberta Villa; Vincenzo Nobile; Ortensia Ilaria Parisi; Chiara Lirangi; Fabio Amone; Erminia D’Ambrosio; Nuria Caturla; Jonathan Jones (Applied Sciences)
Adequate sleep is important for learning and memory in children and adolescents. Sleep disorder prevalence is high in adolescents, as well as stress, and both can affect their mental and physical health. To this end, the objective of this study is to evaluate the effectiveness of an herb extract, specifically lemon verbena (Lippia citrodora), in reducing stress and improving sleep quality in healthy adolescents. This study lasted 3 months, during which they filled out the Adolescent Sleep Wake Scale (ASWS) and Perceived Stress Scale for Children (PSS-C) questionnaires, and saliva samples were taken to analyze cortisol levels. Also, a psychologist evaluated the results of this study for each subject and concluded if they considered the treatment to be clinically relevant. As a result, significant improvements versus placebo were detected in the ASWS and PSS-C, starting in the first month of treatment, coinciding with a significant reduction in cortisol levels. The psychologist assessment agreed that the treatment was successful for 86% of the experimental group, compared to only 19% of the placebo group. In conclusion, the results of this study revealed that the product may help reduce stress and improve sleep quality in adolescents with sleep and stress issues.